2022
DOI: 10.1148/radiol.2021211241
|View full text |Cite|
|
Sign up to set email alerts
|

U.S. Diagnostic Reference Levels and Achievable Doses for 10 Pediatric CT Examinations

Abstract: Background: Diagnostic reference levels (DRLs) and achievable doses (ADs) were developed for the 10 most commonly performed pediatric CT examinations in the United States using the American College of Radiology Dose Index Registry.Purpose: To develop robust, current, national DRLs and ADs for the 10 most commonly performed pediatric CT examinations as a function of patient age and size.Materials and Methods: Data on 10 pediatric (ie, patients aged 18 years and younger) CT examinations performed between 2016 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 21 publications
2
24
1
Order By: Relevance
“…The studies of Takei et al, 8 Kanal et al, 12 and Vawda et al 15 showed that DRLs and ADs for size-based CTDIvol, SSDE, and DLP for body evaluations increased in lockstep with the patient's effective diameter. Kanal et al 12 indicated that CTDIvol was higher when facilities used a tube voltage of 120 kV as a pediatric CT scanning condition. However, using 80 to 100 kV can help reduce CTDIvol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies of Takei et al, 8 Kanal et al, 12 and Vawda et al 15 showed that DRLs and ADs for size-based CTDIvol, SSDE, and DLP for body evaluations increased in lockstep with the patient's effective diameter. Kanal et al 12 indicated that CTDIvol was higher when facilities used a tube voltage of 120 kV as a pediatric CT scanning condition. However, using 80 to 100 kV can help reduce CTDIvol.…”
Section: Discussionmentioning
confidence: 99%
“…The age-based CTDIvol AD ranged from 19 to 46 mGy for heads without contrast material, and the DRL ranged from 23 to 55 mGy, with both AD and DRL increasing with age. Using data from the American College of Radiology Dose Index Registry, diagnostic reference values and realistic doses for the 10 most often performed CT pediatric examinations were produced as a function of patient age and effective diameter 12 …”
mentioning
confidence: 99%
“… 18–21 However, these NDRLs are for age groups or weight groups different from those proposed in the European guidelines. In a recent study performed in the USA, 22 DRL was determined for several CT examinations. However, as information about patient weight was not available in the study, age groups were converted to weight groups.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, optimizing the radiation dose for pediatric CT is a priority. In children, CT is most frequently used for brain imaging [ 2 , 3 ], and an increased incidence of brain tumors has been reported in children who underwent brain CT [ 4 , 5 , 6 ]. Therefore, optimization of the radiation dose in pediatric brain CT is of particular importance.…”
Section: Introductionmentioning
confidence: 99%